Prediction of Premature Ovarian Insuffi ciency and prevalence of medical diseases - El-Jabu H; Elfortia I; Andisha A; Gerriw B; Ben-Saleh H; Abukail R; Mlitan H; El-Gomati E; Elmahjoob E (Global Journal of Fertility and Research - Peertechz Publications, 2019)
Background: Premature Ovarian Failure (POF) represents 1% among women below the age of 40 and can be diagnosed by two levels of serum Follicular Stimulating Hormone (FSH) ≥40mIU/mlat 6 weeks apart. There are many reasons for POF and commonly is idiopathic (60% to 80%). POF has a negative impact on the psychological, social and quality of life of females. Objective: This study aims to find the possibility of prediction of Premature Ovarian Insufficiency (POI) and its relation to medical disorders. Materials and methods: A retrospective study was conducted at the National Center for Diagnosis and Treatment of Infertility- Misurata, Libya. A total of 350 patients with POI were involved. The Inclusion Criteria were: age <40 years, with high serum FSH level, low Anti-Mullrian Hormone (AMH) and low Antra-Follicular Count (AFC). The hormonal essay including FSH, Luteinzing Hormone (LH), Estradiol (E2), Thyroid-Stimulating Hormone (TSH), Prolactin and Fasting Blood Sugar (FBS) along with the medical history was collected. Results: Overall collected cases had a mean age (31.19±3.86 years) and the medical disorders represented 47% of POI causes. Hypothyroidism, Hyperprolactinemia and Diabetes Mellitus were the most common associated disorders (31%, 30%, 14% respectively). The increase in the level of FSH (14.78±12.87) was the most sensitive test to predict POI especially in hypothyroidism cases, which could help to predict ovarian failure in those groups of people. Conclusion: There is a strong association between POI and medical conditions especially Hypothyroidism. Changes in FSH are the most sensitive test among ovarian markers to predict POF.